2014
DOI: 10.1002/jso.23832
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of health‐related quality of life issues in locally recurrent rectal cancer

Abstract: The standardization of surgical techniques supplemented with appropriate neoadjuvant chemoradiation has led to the decline in local recurrence rates of rectal cancer (LRRC) from 25-50% to 5-10%. The outcomes reported for surgical intervention in LRRC is encouraging, however, a number of controversies exist especially in the ultra-advanced and palliative setting. Incorporating health-related quality of life (HRQoL) outcomes in this field could supplement traditional clinical endpoints in assessing the effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…27,28 Survivors with permanent ostomies are also more likely to experience social distress post-treatment. 29 Similar to other studies 4,5 , we found a high prevalence of persistent sexual dysfunction associated symptoms in both female and male survivors regardless of ostomy status. This suggests that problems with the physiologic functionality that impact sexual function are universal for all RC survivors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…27,28 Survivors with permanent ostomies are also more likely to experience social distress post-treatment. 29 Similar to other studies 4,5 , we found a high prevalence of persistent sexual dysfunction associated symptoms in both female and male survivors regardless of ostomy status. This suggests that problems with the physiologic functionality that impact sexual function are universal for all RC survivors.…”
Section: Discussionsupporting
confidence: 89%
“…This has been suggested previously 4,5 , although the absence of sexual activity may not be an accurate reflection of physiologic functionality or the presence of associated symptoms. 6 Lack of sexual activity after surgery with a permanent ostomy can likely be psychogenic or be a result of functional disorders such as erectile dysfunction.…”
Section: Discussionmentioning
confidence: 76%
“…Several studies have demonstrated that pelvic failure significantly affects patient quality of life in terms of fatigue, nausea/vomiting, and pain. [1517] According to a study by Wong et al [17] , >80% of patients with locally recurrent rectal cancer experienced severe pain, and approximately 25% of them experienced bleeding, discharge, and urinary problems, which could significantly impact quality of life. Our results indicated that adjuvant RT did not increase OS or DFS times of patients with stage IV rectal cancer; however, it did have potential oncologic benefits in terms of reducing the risk of local recurrence, which could be important for improving patient quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative chemotherapy offers limited benefit (Harris et al, 2016). Following surgery of this nature, quality of life is satisfactory and superior to non-surgical palliation (Harji et al, 2015).…”
Section: Preoperative Chemotherapy To Downstage Tumours Has Little Vamentioning
confidence: 99%